2016
DOI: 10.1128/mcb.00722-15
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose YY1 Deficiency Activates Expression of Secreted Proteins Linked to Energy Expenditure and Prevents Diet-Induced Obesity

Abstract: Mitochondrial oxidative and thermogenic functions in brown and beige adipose tissues modulate rates of energy expenditure. It is unclear, however, how beige or white adipose tissue contributes to brown fat thermogenic function or compensates for partial deficiencies in this tissue and protects against obesity. Here, we show that the transcription factor Yin Yang 1 (YY1) in brown adipose tissue activates the canonical thermogenic and uncoupling gene expression program. In contrast, YY1 represses a series of sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 59 publications
2
27
2
Order By: Relevance
“…In the present study, we found that GDF15 is released by brown and beige adipocytes in concert with the thermogenic activation of these cells. This confirmed previous observations by Verdeguer et al (27). GDF15 expression shares a strong transcriptional regulation in response to noradrenergic, β3-adrenergic-mediated pathways, involving cAMP, with other intracellular thermogenic machinery components (e.g., UCP1) and with previously identified brown adipokines (e.g., FGF21, bone morphogenetic protein 8B).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we found that GDF15 is released by brown and beige adipocytes in concert with the thermogenic activation of these cells. This confirmed previous observations by Verdeguer et al (27). GDF15 expression shares a strong transcriptional regulation in response to noradrenergic, β3-adrenergic-mediated pathways, involving cAMP, with other intracellular thermogenic machinery components (e.g., UCP1) and with previously identified brown adipokines (e.g., FGF21, bone morphogenetic protein 8B).…”
Section: Discussionsupporting
confidence: 91%
“…This CpG site has recently been characterized as an LEP interaction region (chr7: 127,854,840-127,881,330). Also based on ENCODE data, cg15758240 is in the vicinity of a number of transcription factor binding sites, including YY1 (−99 bp), CEBPB (−144 bp), USF1 (−164 bp), STAT3 (−184 bp), and GATA2 (−204 bp), which has been previously linked to obesity [36][37][38][39][40], suggesting that cg15758240 is located within a genomic region relevant for both fat accretion and transcriptional regulation activity. Hence, we herein add to the current evidence that the harmful effects of maternal hyperglycemia on offspring adiposity and obesity risk is likely to include epigenetic dysregulation of the leptin gene pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, BMP8b, a member of the Bmp protein family, was identified as a brown adipokine released by brown adipocytes in response to noradrenergically mediated thermogenic stimulus (Whittle et al 2012). Further studies have confirmed that Bmp8b is among the most intensely upregulated genes in murine brown adipocytes exposed to thermogenic stimuli (Verdeguer et al 2015, Quesada-López et al 2016. In contrast with other members of the Bmp family, the role of BMP8b in brown adipocyte biology is not associated with the early stages of adipogenic differentiation but with the secretory activity of fully differentiated brown adipocytes.…”
Section: Bmp8b a Key Brown Adipokine For The Adaptive Remodelling Ofmentioning
confidence: 99%
“…Recently, GDF15 has been reported to exert anorexigenic effects through its action at the brainstem and to contribute towards controlling the energy balance (Breit et al 2017. GDF15 is intensely secreted by brown fat upon exposure to cold conditions and by brown adipocytes after noradrenergic stimulation (Verdeguer et al 2015, Campderros et al 2019 and exerts mostly autocrine effects on macrophages, tuning down their pro-inflammatory responses (Campderros et al 2019). Whether these signalling capacities of brown adipokines towards immune cells are restricted to the local cross-talk between immune cells and adipocytes at adipose depots or have consequences on the systemic immune status of the organism are challenging possibilities that remain to be ascertained in further researches.…”
Section: Immune Cells Novel Targets Of Batokines: the Chemokine C-x-mentioning
confidence: 99%